2018
DOI: 10.17221/12/2018-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of the inclusion of white lupine seeds and different types of binders on the blood indicators of young Dwarf Lop rabbits

Abstract: The aim of the present study was to evaluate the effects of the inclusion of whole seeds of white lupine and different binder types in complete pelleted diets on selected haematological and plasma biochemical indicators of growing dwarf rabbits. The individual litters of Dwarf Lop rabbit kits were randomised after birth into control (n = 12) and experimental (E) groups. The young rabbits of the E group (n = 24) received an experimental pre-weaning diet containing a 25% share of white lupine seeds. At the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Damage of cells, hepatocytes in particular, leads to their leakage from damaged cells, which increases their level in blood plasma [39]. According to Šimek et al [40], diet supplementation with white lupin seeds can have a positive impact on the life cycle of cells by protecting them against excess degradation, which was confirmed in the present study wherein blood levels of ASPAT and ALAT were shown to decrease (Experiment II).…”
Section: Discussionsupporting
confidence: 83%
“…Damage of cells, hepatocytes in particular, leads to their leakage from damaged cells, which increases their level in blood plasma [39]. According to Šimek et al [40], diet supplementation with white lupin seeds can have a positive impact on the life cycle of cells by protecting them against excess degradation, which was confirmed in the present study wherein blood levels of ASPAT and ALAT were shown to decrease (Experiment II).…”
Section: Discussionsupporting
confidence: 83%
“…The dietary effect of white lupine seeds on the blood biochemistry profile of hybrid mallard ducks, including an assessment of the serum protein fractions, has not yet been reported in the literature. Since previous studies have proven the dietary effects of lupine seeds on some biochemical indicators in chickens (Viveros et al 2007) and other animals (Martins et al 2005;Bettzieche et al 2008;Simek et al 2018), it can be expected that this effect exists also in fattening ducks. For that reason, the purpose of the present study was to assess the dietary effect of partial (50%) and complete replacement of soybean meal with meal of whole seeds of white lupine, Zulika variety, on selected blood plasma biochemistry indicators and serum protein fractions of Cherry Valley ducks undergoing fattening at the age of 40 days.…”
mentioning
confidence: 99%
“…Besides that, within both trials of the present study, the males showed a higher plasma Glu concentration compared to https://doi.org/10.17221/27/2020-VETMED (2019) in broilers and also by Jerabek et al (2018) in fattened meat-type mallard ducks, when likewise the partial or complete dietary replacement of the SBM with the meal from whole WL seeds was used. Simek et al (2018) found that partial dietary inclusion of WL seeds also showed a TAGlowering effect in pet rabbits. Recently, Bettzieche et al (2008) revealed that the TAG-lowering effect of lupin seeds is caused by the downregulation of the fatty acid synthesis genes and the upregulation of the genes involved in the TAG hydrolysis.…”
Section: Discussionmentioning
confidence: 95%